Impact of PrEP on a STI clinic in a Belgian context: a provider's perspective. Issue 6 (2nd November 2021) - Apers, Ludwig; Vanhamel, Jef; Caluwaerts, Séverine; Platteau, Tom; Kenyon, Chris; Florence, Eric
ABSTRACT: Objectives : To assess the impact of Pre-Exposure Prophylaxis (PrEP) to avoid HIV infection as an additional service in a routine Sexually Transmitted Infections (STI) clinic.Methods : We used routinely obtained retrospective data to estimate the increased workload on the existing facilities. We focussed on STI registration through the laboratory registration system and put this in a national perspective. A critical appraisal was made of the national HIV notifications, as an indicator of the impact of PrEP. Additional challenges were identified via face-to-face interviews with clinicians with at least five years experience in the STI clinic.Results : PrEP delivery puts a substantial burden on a routine STI clinic, in terms of counselling users and prescribing drugs, and regular screening and treating of STIs. Psycho-social aspects need to be incorporated as part of a comprehensive approach of the PrEP user. This requires skills and resources that are not yet always available in a clinic, specialised in HIV and STI care. The increasing demand for this service calls for a careful and critical appraisal of the existing service model.Conclusion : PrEP has gained an important and irreplaceable position in the prevention of HIV infection. New models of care need to be studied, preferably in close collaboration with the users, to make this intervention sustainable for the health system in which it is introduced.